Hubungan Kualitas Layanan Elektronik SIMRS dengan Kinerja SDM di RS X - Alifiani Dewintha Putri; Sarah Geltri Harahap; Catherine Hermawan Salim (Jurnal Kesehatan Amanah, 2025)
The quality of SIMRS electronic services is expected to make the performance of existing human resources at Hospital X work optimally. Hospital services have entered the digitalization era, where all human resources are required to be able to operate the system used. This study aims to see whether there is a relationship between system quality and human resource performance at Hospital X, because now services are done digitally. The sampling technique used total sampling with a total of 53 respondents. The data in this study were analyzed univariately to see the picture per indicator and bivariate analysis with Spearman correlation to see the relationship. The results of the study showed that the relationship between the two variables is interconnected with a high correlation level of 0.700 with a p-value of 0.01. The results of the existing data indicate that the quality of SIMRS has a positive and statistically significant relationship with human resource performance. The results of the study from looking at the relationship between system quality indicators and human resource performance show a relationship between 3 of the 4 indicators with human resource performance. These indicators are system flexibility, system integrity, and response time